2022
DOI: 10.1038/s41467-022-29068-z
|View full text |Cite|
|
Sign up to set email alerts
|

The Oligodendrocyte Transcription Factor 2 OLIG2 regulates transcriptional repression during myelinogenesis in rodents

Abstract: OLIG2 is a transcription factor that activates the expression of myelin-associated genes in the oligodendrocyte-lineage cells. However, the mechanisms of myelin gene inactivation are unclear. Here, we uncover a non-canonical function of OLIG2 in transcriptional repression to modulate myelinogenesis by functionally interacting with tri-methyltransferase SETDB1. Immunoprecipitation and chromatin-immunoprecipitation assays show that OLIG2 recruits SETDB1 for H3K9me3 modification on the Sox11 gene, which leads to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 61 publications
1
20
0
Order By: Relevance
“…In addition, as seen in zebrafish optic tectum, a subtype of OPCs remain precursors throughout life and control axonal remodeling, never differentiating into myelinating oligodendrocytes (Xiao et al, 2022). A recent study has demonstrated that a set of genes, involved in pathways including neuronal differentiation and brain development, are repressed by Olig2 to ensure OPC differentiation into oligodendrocytes (K. Zhang et al, 2022). Therefore, it is tempting to speculate that OPCs switch off Olig2 expression and remain as precursors or NG2 glia upon the change of brain activity.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, as seen in zebrafish optic tectum, a subtype of OPCs remain precursors throughout life and control axonal remodeling, never differentiating into myelinating oligodendrocytes (Xiao et al, 2022). A recent study has demonstrated that a set of genes, involved in pathways including neuronal differentiation and brain development, are repressed by Olig2 to ensure OPC differentiation into oligodendrocytes (K. Zhang et al, 2022). Therefore, it is tempting to speculate that OPCs switch off Olig2 expression and remain as precursors or NG2 glia upon the change of brain activity.…”
Section: Discussionmentioning
confidence: 99%
“…Zhou et al, 2015). Regions lowly demethylated in oligodendrocytes were enriched for the motif of Olig2, a wellstudied master regulator of oligodendrocyte cell identity (K. Zhang et al, 2022;Q. Zhou et al, 2000), as well as Tcf12, which may be involved in the known generation of oligodendrocyte-fated NSCs by Wnt ligands (Ortega et al, 2013).…”
Section: Adult Nsc Differentiation Includes Two Waves Of Dna Methylat...mentioning
confidence: 99%
“…Zhou et al, 2015). Regions lowly demethylated in oligodendrocytes were enriched for the motif of Olig2, a well-studied master regulator of oligodendrocyte cell identity (K. Zhang et al, 2022; Q.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect can be reversed by using a physiological antagonist of BMP4, such as noggin, which may restore differentiation [ 91 , 106 , 107 ]. OLIG2 appears to interact with a variety of factors, such as ASCL1, BRG1, transcription factor 4 (TCF4), and SET domain bifurcated histone lysine methyltransferase 1 (SETDB1) to ensure proper OPCs differentiation [ 108 , 109 , 110 , 111 , 112 ]. G protein-coupled receptor 17 (GPR17) can act as a downregulator of OLIG1 that negatively controls the maturation and coordinates the generation of myelinating OLs from pre-myelinating OLs through ID proteins [ 113 ].…”
Section: Myelinogenesis and Myelin Development: A Spatiotemporal Coor...mentioning
confidence: 99%